2009
DOI: 10.1029/2008ja013704
|View full text |Cite
|
Sign up to set email alerts
|

Quiescent current sheets in the solar wind and origins of slow wind

Abstract: [1] Solar wind near the heliospheric current sheet is investigated using Ulysses and ACE data in a superposed epoch analysis for several days on either side of the current sheets. Only data near sunspot minima are used, minimizing the influence of transients. New results are shown for composition and ionization state. Existing results showing a $2 day wide depletion in He/H (He ++ /H + ) at the current sheet are confirmed, although the depletion is generally more narrow. A recent finding of a broad 5-10 day wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
72
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 40 publications
6
72
0
Order By: Relevance
“…They reached the conclusion that the He/H depletions originate in the core, or the helmet of the streamer, based on (1) a correlation between He/H and O/H depletions over a two-month interval, which indicate a common region of origin, and (2) depletion in O occuring in the core of streamers relative to the legs according to results obtained with the SOHO/Ultraviolet Coronagraph Spectrometer (Raymond et al 1997;Raymond 2004). Suess et al (2009) attribute the in situ signatures to transient blobs flowing out from the streamer belt and explain the asymmetry across the sector boundary by a difference in velocity.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…They reached the conclusion that the He/H depletions originate in the core, or the helmet of the streamer, based on (1) a correlation between He/H and O/H depletions over a two-month interval, which indicate a common region of origin, and (2) depletion in O occuring in the core of streamers relative to the legs according to results obtained with the SOHO/Ultraviolet Coronagraph Spectrometer (Raymond et al 1997;Raymond 2004). Suess et al (2009) attribute the in situ signatures to transient blobs flowing out from the streamer belt and explain the asymmetry across the sector boundary by a difference in velocity.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, ion composition and charge state distributions are of great importance to help discriminate between plasma origins (chromospheric and coronal, respectively). Recently, Suess et al (2009) showed that depletions in He 2+ with respect to H + abundance (density) are preferentially located on one side of the "quiescent" HCS. They reached the conclusion that the He/H depletions originate in the core, or the helmet of the streamer, based on (1) a correlation between He/H and O/H depletions over a two-month interval, which indicate a common region of origin, and (2) depletion in O occuring in the core of streamers relative to the legs according to results obtained with the SOHO/Ultraviolet Coronagraph Spectrometer (Raymond et al 1997;Raymond 2004).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other variations might be linked to non-uniform compositional signatures at HCS crossings (see Suess et al, 2009). These are items for future study.…”
Section: Stream Interfaces and Solar Origins: Case Study Of Carringtomentioning
confidence: 99%